Developments in Rapid Detection Methods for the Detection of Foodborne Campylobacter in the United States - Ricke, Steven C.; Feye, Kristina M.; Chaney, W. Evan; Shi, Zhaohao; Pavlidis, Hilary; Yang, Yichao (Frontiers in Microbiology, 2019)
The accurate and rapid detection of Campylobacter spp. is critical for optimal surveillance throughout poultry processing in the United States. The further development of highly specific and sensitive assays to detect Campylobacter in poultry matrices have tremendous utility and the potential to aide in the reduction of foodborne illness. The introduction and development of molecular methods such as polymerase chain reaction (PCR) have enhanced the diagnostic capabilities of the food industry to identify the presence of foodborne pathogens throughout poultry production. Further innovations in various methodologies, such as immune-based typing and detection as well as high throughput analyses, will provide important epidemiological data such as the identification of unique or region-specific Campylobacter. Comparable to traditional microbiology and enrichment techniques, molecular techniques/methods have the potential to have improved sensitivity and specificity, as well as speed of data acquisition. This review will focus on the development and application of rapid molecular methods for identifying and quantifying Campylobacter in U.S. Poultry and the emergence of novel methods that are faster and more precise than traditional microbiological techniques.